Designing and developing an e-Outing System as a web-based tracking tool application / Nur Ainatul Mardiah Mat Nawi … [et al.] - Mat Nawi, Nur Ainatul Mardiah; Abdul Rahman, Khadijah; Mohd Said, Muhammad Harif Fazillah; Rozimi, Mohammad Nor Rafiq (UiTM Press, 2022)
The existing outing system still requires a lot of manual effort. Based on the current system, students are required to write down student details including name, matric number, time and date of outing. They then need to get the approval from the College Residents’ Staff (CRS). The process is time consuming. As an initiative, an e-Outing system is suggested as it will help to digitalize the process. This E-Outing System is a web based tracking tool application that helps the administrative staff in organizing and managing the students’ outing records. The aim of this project is to create a web-based system that can manage outing applications and provide an integrated view of the records which help to reduce the time spent in filling out the manual outing application forms. Besides, this system will also notify the parents once the outing application has been approved, ensuring awareness of their child’s activities on that particular day. The other problem identified is the wastage of space storage to keep the data. Thus, this system will provide an online database to store the students’ information. This system is developed following the five stages in System Development Life Cycle (SDLC) which include planning, analysis, design, implementation and maintenance.